Crisis, economic policy and inequality in Spain - de Arriba, Raúl (Papeles de Europa, 2014)
This paper analyses the social impact of both the economic collapse and policies adopted during the crisis in Spain. This crisis has highlighted the fragility of the Spanish economic growth. In addition, both the austerity measures adopted since 2010 as reforms in labour market and welfare state system have worsened the living conditions of the population. The result of this years of crisis and economic policy is an explosive increase in unemployment, reduction of personal incomes, intensifying inequality and increasing poverty.